Analisis Label Halal pada Nama Dagang Obat Tablet Melalui Pengamatan pada Kemasan Sekunder terkait Jaminan Produk Halal di RSI Sultan Agung Semarang - Aditya Dwi Meilani; Martodihardjo, Suwaldi; Ayu Ariessanti, Ida (Sultan Agung Islamic University of Semarang, 2022)
Background: Drug is a substance or mixture of materials used to prevent disease, treat, assist in diagnosis, render infertile or make muscles weak during surgery. The halal medicinal products in the manufacturing process, especially in the manufacturing of tablet drugs, must be free from ingredients containing pork and alcohol. In addition, tablet drugs can be said to be halal if in the production process it is proven that they are free from the critical point of halal medicinal ingredients. The purpose of this study was to find out how many trade names of tablet drugs were distributed by the Sultan Agung Islamic Hospital which included halal labels on the secondary packaging and the critical point of the halal tablet drugs. Methods: This study used an observational descriptive design. Data was collected by observing the secondary packaging of the Tablet Drug Trade Names found in the Hospital Pharmacy Logistics as many as 125 items of tablet drug trade names. The data is processed using tables and calculated the percentage of halal labels that have been listed as well as seeing the critical point of halal for drugs that have not been labeled halal. Results: The results of this study indicate that the inclusion of halal labels distributed by the Sultan Agung Islamic Hospital as many as 21 tablet drug items (16.8%) of the 125 tablet drug items have been labeled with a halal label and the rest have not included a halal label.Conclusion: Some of tablet drugs that are distributed by the Sultan Agung Islamic Hospital are not halal labelled, but still classified as halal drugs based on their composition and have been registered with BPOM.